A differentiated approach to comprehensive surgical treatment of combined combat thermomechanical injuries - Korol, S. O.; Palii, I. P. (General Surgery, 2024)
In recent years, there has been a notable increase in the incidence of thermomechanical injuries, which frequently manifest as a combination of various types of damage. The majority of these injuries require long‑term treatment and result in the development of decompensated (critical) conditions during the early stages, with a substantial death rate ranging from 75% to 80%. Objective — to improve the results of surgery for combined combat thermomechanical injuries by developing and implementing a differentiated surgical approach that incorporates the assessment of injury severity within the context of medical support. Materials and methods. A retrospective‑prospective study was carried out to determine the effectiveness of medical care provided for wounded individuals with combined combat thermomechanical injuries sustained during combat operations between 2017 and 2023. The study included a cohort of 97 wounded individuals, who were subsequently divided into two separate clinical groups. The main group (n=56) underwent treatment according to a differentiated surgical approach that included the assessment of the severity of the patient’s condition using the admission trauma scale (AdTS) and the perfusion index (PI). The control group (n=41) received treatment based on established protocols using conventional treatment approaches for combined combat thermomechanical injuries without considering prioritisation. Results. A differentiated surgical strategy for managing combined combat thermomechanical injuries, which included an objective assessment of injury severity using the AdTS and the perfusion index (PI), allowed for a notable decrease in the occurrence of late purulent‑septic complications as well as a significant reduction in the mortality rate in the main group to 21.4%, compared to 38.8% in the control group (p=0.038). This was related to a decrease in the frequency of fatal outcomes among individuals with serious injuries: 21.2% in the main group, 37.0% in the control group (p=0.013). Furthermore, surgical treatment improved anatomical and functional outcomes in the main group compared to the control group. Group 1 had a higher specific weight of favourable outcomes 52.0±14.2% and a lower specific weight of unsatisfactory outcomes (17.6), [8.7;28.7] %, compared to group 2 20.6±13.4% and 47.3±14.7%. The difference was statistically significant at p=0.001. Conclusions. The implementation of a differentiated surgical approach with an objective assessment of injury severity resulted in a reduction in mortality from 7.3% to 1.8%, specific weight of amputations from 34.2% to 8.9%, and contractures from 26.8% to 10.5% (p<0.05). Early vacuum therapy in the surgical treatment of combined combat thermomechanical injuries reduced treatment time and allowed for early reconstructive and restorative operations, leading to better functional outcomes. The specific weight of favourable outcomes increased from 20.6% to 52.0%, while the relative number of unsatisfactory outcomes decreased from 47.3% to 17.6% (p<0.05).